Próba rekonstrukcji pradziejowego środowiska przyrodniczego - Grzelakowska, Elżbieta (Acta Universitatis Lodziensis. Folia Archaeologica, 1984)
The aim of this article is to present different possibilities of reconstructing the primaeval natural environment on the example of Tuchola Forests as well as the extent to which such reconstruction is possible. It is an obvious fact that ecology exerts an influence on development of social formations, economy types, and the cultural development degree. That is why in researches carried out by archaeologists there are appearing more and more frequently attempts at superimposing the occuring cultural changes on the background of the natural environment conditions in which these changes were taking place. Before proceeding to the reconstruction of the primaeval environment it was necessary to get acquainted with the present conditions prevailing in Tuchola Forest, their geology, geomorphology, fauna and flora. This was followed by analysis of materials provided by pallnological analyses performed on archaeological positions in the area of Tuchola Forest (Obrowo, Iwiec, Cisy Staropolskie, Siwe Bagno, Smoldziny Turbary, Stawek Lake, Odry), and those from the neighbouring areas and belonging to the same geobotanical country (Fletnowo, Radowiska Małe, Mielno near Lipno). The data gathered in this way allowed to reveal changes in the natural environment occuring with the lapse of time. They also allowed to note the dominance of the pine-tree in this area for at least the last 5000 years. The preserved relics of fauna and flora coming from the reservations in Tuchola Forest allowed to trace the big diversity of habitats to be found here and connected with ecological conditions corresponding to them. The paleobotanical analysis of macrofragments produced rather poor data since in the area in question there is known only one position examined by means of this method (Odry). These scarce data allowed to determine a strong correlation between vegetation and geonorphology in this area as well as the time from which changes produced by man's activity should be reckoned with. These changes are more noticeable In the South-Western part of Tuchola Forest where more fertile soils were attracting groups of people earlier and where differentiated natural environment was undergoing bigger changes. These scarce data sources considerably restricted the reconstruction, but despite it such reconstruction seems to be useful in analysing changes In the human settlement process in this area.